Comparisons of alumina barrier films deposited by thermal and plasma atomic layer deposition. (March 2019) - Jarvis, K.L.; Evans, P.J.; Nelson, A.; Triani, G.
Abstract: Barrier films are commonly deposited onto flexible substrates by atomic layer deposition (ALD) to protect organic electronics from degradation due to the ingress of moisture. Both thermal ALD and plasma-enhanced ALD (PEALD) have been used for this purpose, but few comparisons have been made as to which technique produces superior barrier films. In this study, alumina (Al2 O3 ) barrier films have been deposited by thermal ALD and PEALD to investigate the effect of the deposition technique on the water vapor transmission rate (WVTR). Al2 O3 films with thicknesses of approximately 10 or 20 nm were deposited at 100 or 120°C. The chemistry, morphology, and density of the films were investigated with X-ray photoelectron spectroscopy, atomic force microscopy, and X-ray reflectometry respectively. The WVTRs of the films were measured using tritiated water (HTO) permeation at 25°C and 95% relative humidity. Both the thermal and PEALD films had similar Al:O ratios, whereas the PEALD films were slightly smoother than the thermal ALD films. No significant difference in the film densities was observed. All PEALD films had lower WVTRs than their thermally deposited counterparts. The lowest WVTR measured was 4.2 × 10 −2  g m −2 /day for a 17-nm-thick PEALD Al2 O3 film deposited at 120°C. These results indicate the importance of optimizing deposition parameters to enable production of the most effective barrier films, which are essential in applications such as organic electronics. Graphical abstract: Image 1 Highlights: Water vapor transmission rates (WVTRs) compared of Al2 O3 barrier films deposited by thermal atomic layer deposition (ALD) and plasma-enhanced ALD (PEALD). PEALD films were smoother with similar Al:O ratios and densities. PEALD films had lower WVTRs than thermal ALD films. Lowest WVTR of 4.2 × 10 −2  g m −2 /day for a 17-nm-thick PEALD Al2 O3 film deposited at 120°C. Results showed that small changes in films properties significantly influence WVTR.